Spirit of PPL and Practicum in Increasing Students' Interest in Learning at MAS Darul Ikhlas - Ritonga, Syaipuddin; Sir, Abdul Hanif; Nopida, Suci; Nur, Mawarni; Hasibuan, Desi Fitriani; Siregar, Windah Nur; Tambak, Nur Asyifa (AMK : Abdi Masyarakat UIKA, 2024)
The spirit of PPL and Practicum for STAIN MADIN students was very enthusiastic when doing an internship at MAS Darul Ikhlas Dalan Lidang. This PPL was attended by students from across study programs such as PBA, MPI, and PAI. In this PPL, STAIN MADINA students carry out various activity programs to increase students' interest in learning by using learning media, carrying out various activities, and involving students in various activities and events held at STAIN MADINA. Also in the field of Educational Management, carrying out office layout and learning to improve students' interests.